Teachers' coping strategies in mitigating remote learning-related distress during Covid-19 pandemic - Doria, Karen Margarette M.; Ortega-Dela Cruz, Ruth A. (Universitas Airlangga, 2024)
The sudden shift to remote learning during the Covid-19 pandemic has brought much distress to teachers. Since the teachers are considered as the major force that facilitates the learning process, their well-being should be given importance. The study used a survey research design to determine the level of distress among private school teachers in San Pablo City, Philippines, using the Covid-19 Peritraumatic Distress Index (CPDI). It also analyzed the sources of distress and examined the different coping strategies the teachers are using to mitigate the distress related to remote learning. Results show that the majority of the respondents are experiencing distress, with most having mild-moderate distress, followed by severe distress. Preparation of learning materials, internet connectivity problems, limited teacher-student interaction, assessment of student's learning, tracking student's progress, inconducive working environment, and inadequate technical skills were identified as sources of distress. Most respondents prefer coping strategies that would promote their overall wellness and those activities that avoid the source of distress. These findings have implications for school owners and administrators, policymakers, and curriculum developers in addressing the needs of teachers by providing programs that would help them cope with the distress related to remote learning.